Insights into kimberlite petrogenesis and mantle metasomatism from a review of the compositional zoning of olivine in kimberlites worldwide - Giuliani, Andrea (Lithos, 2018)
Olivine is the dominant component in kimberlites (~40–60 vol%), where it occurs as individual grains of variable size (>1 cm to <100 μm) of xenocrystic and magmatic origin. Understanding the processes governing its compositional variations will provide unique insights into the genesis and evolution of kimberlites. The results reviewed here include >2700 major and minor element analyses of olivine from 17 kimberlite localities from southern Africa, Canada, Greenland and Russia. These data show that the large majority of olivine grains in coherent kimberlites are compositionally zoned regardless of size and shape. The zonation typically includes a core of variable composition (e.g., Mg# = 100 × Mg/(Mg + Fe) = 78–95) that is overgrown by a rim characterised by relatively restricted Mg# (typically ≤1 "unit'; predominantly 88–92), decreasing Ni and Cr, and increasing Mn, Ca and Ti contents. One or more internal zones of variable composition occur between core and rim of some grains. The internal zones can be euhedral, diffuse or partially resorbed (i.e. embayments). Low-Ni, high Mg-Ca rinds (Mg# up to 96–98) commonly fringe olivine rims in fresh (i.e. minimally serpentinised) kimberlites. A comparison between the compositions of olivine cores and olivine from mantle xenoliths (including megacrysts) entrained by kimberlites, demonstrates that olivine cores are xenocrysts derived from disaggregation of mantle wall-rocks. This interpretation is consistent with the inclusion of mantle phases (i.e., orthopyroxene, clinopyroxene, garnet and Cr-spinel) in olivine cores, and evidence of resorption (i.e. embayments) and abrasion (e.g., rounded shapes) of these cores. A variable proportion of olivine cores is sourced from the products of kimberlite metasomatism at mantle depths (e.g., sheared peridotites, megacrysts, 'defertilised dunites'), which implies variable extent of kimberlite activity in the mantle before kimberlite emplacement at surface. Olivine rims host inclusions of groundmass minerals (e.g., spinel, ...